Manajemen Supervisi Dalam Lembaga PAUD Di TK Negeri Pembina Nasal - Yosi Melda Sari; Ahmad Huzairin (Universitas PGRI Semarang, 2021)
AbstractThis observation is designed to see the management of supervision in the “PAUD” institution. Supervision of education is an effort to develop and ensure the quality of the performance of teaching and education personnel. It is hoped that the results of this research can contribute to useful thoughts in the future, especially related to supervision in PAUD institutions. The principal, 4 teachers, and school managerial staff were respondents in the research activity. The descriptive-qualitative data collection was carried out through observation, interviews and document study. The supervision program had a positive impact in achieving the planned goals and also found positive responses from teachers and several follow-up plans. Furthermore, this study provides recommendations for improving the internal supervision program, regarding management, and the idea of supervision in PAUD institutions for future research. The conclusion of this study is that the supervision activities carried out at TK Negeri Pembina Nasal have been carried out in a structured and well-planned manner with planning, implementation, evaluation, and follow-up steps. A pleasant, open and democratic attitude is the principle in the implementation of this supervision activity. Apart from that there is also public confidence in the quality and performance of teachers at Nasal Pembina Kindergarten. This is what encourages the head of TK Negeri Pembina Nasal to always evaluate academic supervision programs in maintaining trust and improving the quality of teacher performance in improving learning.Keyword : management, supervision, PAUDAbstrakPengamatan ini dirancang untuk melihat manajemen supervisi pada lembaga “PAUD” Supervisi pada pendidikan merupakan upaya mengembangkan dan menjamin kualitas kinerja tenaga pendidik dan kependidikan. Diharapkan penelitian ini hasilnya dapat menjadi sumbangsih pemikiran yang bermanfaat dimasa yang akan datang khususnya terkait supervisi dalam satuan lembaga PAUD. Kepala sekolah, 4 orang guru, dan staf manajerial sekolah merupakan responden dalam kegiatan peneliti. Pengumpulan data deskriptif-kualitatif ini dilakukan melalui pengamatan, wawancara dan studi dokumen. Program supervisi berdampak positif guna mencapai tujuan yang direncanakan dan juga ditemukan tanggapan positif guru dan beberapa rencana tindak lanjut. Selanjutnya studi ini memberi rekomendasi untuk meningkatkan program supervisi internal, tentang manajemen, dan gagasan supervisi dalam lembaga PAUD untuk penelitian dimasa depan. Kesimpulan dari penelitian ini bahwa kegiatan supervisi yang dilaksanakan di TK Negeri Pembina Nasal telah dilakukan secara terstuktur dan terencana sedemikian baiknya dengan langkah perencanaan, pelaksanaan, evaluasi, dan juga tindak lanjut. Sikap menyenangkan, terbuka dan demokratis merupakan prinsip dalam pelaksanaan kegiatan supervisi ini. Selain dari pada itu terdapat juga kepercayaan masyarakat terhadap kualitas dan kinerja guru pada TK Negeri Pembina Nasal. Hal Ini yang mendorong kepala TK Negeri Pembina Nasal untuk selalu mengevaluasi program supervisi akademik dalam menjaga kepercayaan dan meningkatkan kualitas kinerja guru dalam meningkatkan pembelajaran.Kata Kunci : manajemen, supervisi, PAUD